The Influence of the Roundtable Learning Model on the Writing Skills of Fourth Grade Students at SDN 01 Simabur - Overa, Syukra Wati; Hendriani, Suswati; Ratmiati, Ratmiati (CV Berkah Syahdin Trust, 2025)
This research is motivated by the low writing skills of students in writing essays, students have difficulty in developing ideas or concepts in writing according to the predetermined theme, students admit that they are less interested in learning to write, because it tends to be boring. This study aims to determine the effect of the roundtable learning model on the writing skills of fourth grade students of SDN 01 Simabur. The type of research used is quantitative experiment one group pretest-posttest design. In this study, the population was fourth grade students of SDN 01 Simabur, with a sample size of 15 people. The sampling technique in this study used Purposive Sampling. Data collection in this study used a writing test instrument. By using the initial test (pretest) and final test (posttest). The data analysis techniques used are the normality test and homogeneity test, then conducting a hypothesis test using the t-test. The results of the study showed that there was an influence of the roundtable learning model on the writing skills of grade IV students of SDN 01 Simabur, this was evidenced by the output of the Paired Sample T-test table above, the Sig value (2-tailed) was 0.000 <0.05, so according to the decision making of the hypothesis test, it can be concluded that Ho is rejected and Ha is accepted. This means that there is an Influence of the Roundtable Learning Model on the Writing Skills of Grade IV Students of SDN 01 Simabur.